Influence of turning methods on temperature profile of button mushroom compost pile - Arumuganathan, T; Tewari, R P; Kamal, Shwet; Kumar, Rajesh; Ramanathan, M (Mushroom Research, 2018)
Button mushroom (Agaricus bisporus (Lange) Sing.) produces high quantity and superior quality protein from the huge quantity of agro wastes through the process called composting. The purpose of composting is to convert a rich mixture of organic materials into a satisfactory and stable medium suitable for the growth of button mushroom. As the required quality standards of the mushroom compost are not achieved in manual operations, a compost turner of capacity 5 tonnes per hour was designed and developed to turn the compost mechanically. Two types of major agricultural waste materials viz., wheat straw, paddy straw and its mixture wheat straw + paddy straw (1:1) were selected as raw materials for composting. The temperature profile of compost prepared using compost turner was compared with the temperature profile of compost prepared manually following the traditional long method of composting. The compost piles turned using compost turner recorded higher temperatures than the manual one.